AN ERROR ANALYSIS ON USING SIMPLE PAST TENSE IN WRITING ENGLISH COMPOSITION - Ferdiyanto, Feri (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2023)
Writing in English is actually difficult for some students and learners. When they use the language in writing, they might run into problems. It is for this reason that their writing will contain errors. Writing in English is governed by rules, which can make learning the language difficult. Drawing on the qualitative lens, the current study has attempted to investigate the errors on using simple past tense in writing English composition. Twenty students voluntarily participated in this study as the research participants. The data indicated that while writing English composition in the simple past tense, grammar is the most challenging. The verb that was contained in the regular and irregular, preposition, determiner, and noun was incorrect. The researcher discovered that students become confused when they employ spelling correctly when composing written work. This occured because the students wrote a word without first looking it up in their dictionary. Punctuation is included last. The children are still unsure about when to use a full stop and comma in their writing.